Discrepancies in meeting OREO guidelines: The Teacher-researcher’s sacrifice and new skill set needs - Oscar Ndayizeye (EKSPOSE, 2021)
In this evaluation research, the researcher aimed at examining the extent to which Hebei Foreign Studies University (hereafter referred to HFSU) implementated of the O.R.E.O guidelines during COVID-19 lockdown. To collect data, the researcher used the document analysis, an interrater checklist, and participant observation. As the study used both the qualitative and quantitative data, the analysis was equally qualitative and descriptive statistics was used to analyse quantitative data. The major findings were that HFSU did well as two raters found out that fourteen criteria out of sixteen on the rating metrics were fulfilled. The level of O.R.E.O implementation of that university during the Covid-19 lockdown (Semester I, academic year 2020-2021) is “Very Highly” (92%) but it could have done more than that by adjusting few things like insuring undisturbed learning space by parents or guardians and cross-checking information reported both by students and teachers concerning the daily activities of the online teaching-learning.